المسؤولية الإجتماعية في تحليلات مدخل النسق الإجتماعي الفني - ربوش العارفة (University of Eloued جامعة الوادي, 2024)
Abstract: The study aims at analyzing the postulates and concepts of the tehnical social set up trend to investigate and identify the types of responsibility in each theory, so as to carefully implement the belief that “social theory is comprehensive for all social phenomena,” including the phenomenon of social responsibility within the institution that represents an open set up according to the modern approach in studies of strategy and labour sociology in order to result in four types of social responsibility, which are included in the entrance of the technical social pattern. These are ; technological responsibility, automated responsibility, flexible responsibility, and integrated responsibility so that each of these types of responsibilities is exercised in an organizational environment characterized by certain conditions.
مقاربة سسيولوجية
Keywords: tehnical social pattern; social responsibility; environment; technology; Organizational structure; النسق الإجتماعي الفني; المسؤولية الإجتماعية; الهيكل التنظيمي